CONSTRUCTION OF GENDER EQUALITY: ANALYSIS OF JACQUES LACAN'S PSYCHOANALYTIC THEORY ON AMINA WADUD'S THOUGHTS - Nadhiraturrahmi Aidina; Nada Rahmatina; Rijal Ali (Takafu: Journal of Tafsir and Gender Perspective, 2024)
This study aims to examine Amina Wadud’s thoughts in her interpretation of the Qur'an using Jacques Lacan’s psychoanalytic approach. The literature review research method is used as a research approach that involves various sources of literature, including Amina Wadud’s works, especially “Qur'an and Woman: Rereading the Sacred Text from a Woman’s Perspective,” as well as related literature that discusses Lacan's thoughts, Islamic feminism, and the interpretation of the Qur'an. Based on Lacan’s mirror stage and his psychoanalytic concepts to analyze the construction of Amina Wadud’s self-identity and gender roles in the interpretation of the Qur'an, it is found in the results of this study that there is identification related to gender identity, inequality, and rejection of patriarchal traditions in Amina Wadud’s thoughts reflected in her interpretation. One of them is in QS. Al-Nisā [4]: ​​1, showing the construction of Amina Wadud’s self-identity and gender roles in the interpretation of the Qur'an.